MENGANALISIS DATA SISWA SISWI RA SHIRATHAL HAQ DALAM PENINGKATAN DAN PENURUNAN SISWA SISWI DARI TAHUN KE TAHUN MENGGUNAKAN POWER BUSINESS INTELLEGENCE - nurul, nurul hidayah (PT. ZIVANA CENDEKIAWAN BANGSA, 2025)
Business Intelligence (BI) is a system or application that plays a role in managing data in a company or organization with the aim of producing relevant information. The world of education is currently in a period of transition where there are many changes and adjustments in all aspects of the education sector, the number of new student registrants RA SHIRATHAL HAQ has experienced significant ups and downs over the last five periods, Due to the increasing competitiveness between schools, schools also provide advantages that other schools rarely have, so that parents are more interested in sending their children to RA SHIRATHAL HAQ, Therefore, the school implements a system of cultivating the islamic spirit of children, a difficult rule in improving the quality of children’s education in indonesia, especially in the Tembilahan area. Apart from this, especially for each kindergarten school, each kindergarten improves the quality of education in each school, one of which is this school implementing system of cultivating the islamic spirit of children in order to attract the interest of parents to register their children in this RA SHIRATHAL HAQ. This research will use POWER BUSINESS INTELLIGENCE which includes stages in resolving this case, and from this data research it can be hoped that it will make it easier for schools to collect data every year, so they can find out if there is an increase of decrease. This research is expected to produce predictions or temporary analysis to increase the number of registrants to make it easier for schools to analyze developments from year to year to find out accurate information, so that schools can further increase their target of increasing promotion when accepting new students.